The sanitary practices of the residents and coliform analysis of deep well water of Barangay Sirang Lupa Calamba Laguna - Casalme, Dessa Jean O. (2013)
This descriptive research determines the quality of deepwell water in Barangay Siranglupa and the sanitary practices among its residents. Five hundred (500) mL water samples from six (6) stations namely, near the quarry, residential, market, school and industrial sites were collected and analyzed using Multiple Tube Fermentation technique to determine the total coliform and E coli count (MPN/100ml). All samples are within the allowable limit for the E.coli (<1.1MPN/100ml). However, elevated risk of waterborne diseases manifested due to significant increased in total coliform count. The sites were ranked as follows Quarry 1=Market=School=Residential > Quarry 2> Industrial site. Majority of the people get their drinking water from deepwell and store them in tin containers. Segregation is not done in most of the household and drainage system is usually stagnant. Livestock were also prominent in the backyard of the residents. Such sanitary practices elevated the risks of contamination with pathogens.